Delineating the Role of Histamine-1- and -4-Receptors in a Mouse Model of Th2-Dependent Antigen-Specific Skin Inflammation - Mahapatra, Subhashree; Albrecht, Melanie; Behrens, Barbara; Jirmo, Adan; Behrens, Georg; Hartwig, Christina; Neumann, Detlef; Raap, Ulrike; Bähre, Heike; Herrick, Christina; Dittrich, Anna-Maria (PLOS ONE, 2014)
Background Histamine drives pruritus in allergic skin diseases which clinically constitutes a most disruptive symptom. Skin pathology in allergic skin diseases is crucially influenced by different T-helper subsets. However, the contribution of different histamine-receptors to T-helper cell dependent skin pathology has not been definitively answered. Models which can specifically address the functional role of T-helper subsets and the mediators involved are therefore valuable to gain further insights into molecular pathways which contribute to allergic skin disease. They might also be helpful to probe amendable therapeutic interventions such as histamine-receptor antagonism. Objective Establishing an adoptive transfer model for antigen-specific Th cells, we aimed to delineate the role of histamine H1- and H4-receptors in Th2-dependent skin inflammation. Methods In-vitro differentiated and OVA primed Th2 cells were adoptively transferred into congenic recipient mice. In vivo treatment with specific histamine H1- and H4-receptor antagonists was performed to analyze the contribution of these histamine-receptors to Th2-dependent skin pathology in our model. Analysis four days after epicutaneous challenge comprised skin histology, flow cytometric detection of transferred T-helper cells and analysis of antigen-cytokine profiles in skin-draining lymph nodes. Results Use of specific H1- and H4-receptor antagonists revealed a crucial role for H1- and H4-receptors for Th2 migration and cytokine secretion in a Th2-driven model of skin inflammation. While H1- and H4-receptor antagonists both reduced Th2 recruitment to the site of challenge, local cytokine responses in skin-draining lymph nodes were only reduced by the combined application of H1- and H4-receptor antagonists and mast cell counts remained altogether unchanged by either H1R-, H4R- or combined antagonism. Conclusion Our model demonstrates a role for H1- and H4-receptors in Th2 cell infiltration and cytokine secretion in allergic skin diseases and suggests further studies to evaluate these findings for therapeutic approaches.